Penerapan PBL Untuk Meningkatkan Hasil Belajar Matematika Materi Bangun Datar Kelas IV SDN Dukuh Kupang V - Lailatul Fitria; Jarmani Jarmani; Endang Supriyatin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study aims to improve the mathematics learning outcomes of 4th grade students of SDN Dukuh Kupang V, Panguragan District, Cirebon Regency Semester 2 of the 2022/2023 academic year by using the Problem Based Learning model. This research is a classroom action research (PTK) conducted in two cycles. The subjects in this study were 4th grade students of SDN Dukuh Kupang V Surabayai, totaling 30 students. The variables in this study consisted of independent variables, namely the Problem Based Learning model and the dependentvariable, namely math learning outcomes. Data collection techniques using test techniques. Data analysis techniques using comparative descriptive in the form of percentages of math learning outcomes in pre-cycle, cycle I and cycle II. Based on the results of the study, it can be concluded that learning with the Problem Based Learning model can improve learning outcomes in mathematics subjects on the perimeter area of flat shapes. The results before the action was taken,namely in the pre-cycle only 13 students or 43% were complete, in cycle I increased to 21 studentsor 70% who completed learning math and in cycle II increased again to 26 students or 86% who completed learning. This research is said to be successful because it reaches the performance indicator which is > 80% of all students with KKM 70.